The Reliability of Patient Self-reported Utilization in an Inflammatory Bowel Diseases Learning Health System. Issue 3 (9th June 2021) - van Deen, Welmoed K; Freundlich, Noah; Kwon, Michelle H; Patel, Devin B; Crate, Damara J; Oberai, Ridhima; Shah, Samir A; Hwang, Caroline; Weaver, S Alandra; Siegel, Corey A; Melmed, Gil Y
Abstract: Background: Inflammatory bowel disease (IBD) care is beset with substantial practice variation. Learning health systems (LHSs) aim to learn from this variation and improve quality of care by sharing feedback and improvement strategies within the LHS. Obtaining accurate information on outcomes and quality of care is a priority for LHS, which often includes patients' self-reported data. While prior work has shown that patients can accurately report their diagnosis and surgical history, little is known about their ability to self-report recent healthcare utilization, medication use, and vaccination status. Methods: We compared patient self-reported data within the IBD Qorus LHS regarding recent IBD-related emergency department (ED) visits, hospitalizations, computerized tomography (CT) scans, corticosteroid use, opioid use, influenza vaccinations, and pneumococcal vaccinations with electronic health record (EHR) data. Results: We compared 328 patient self-reports to data extracted from the EHR. Sensitivity was moderate-to-high for ED visits, hospitalizations, and CT scans (76%, 87%, and 87%, respectively), sensitivity was lower for medication use with 71% sensitivity for corticosteroid use and only 50% sensitivity for self-reported use of opioids. Vaccinations were reported with high sensitivity, but overall agreement was low as many patients reported vaccinations that were not registered in the EHR. Conclusions: Self-reported IBD-related ED visits, hospitalizations, and CT scans are reported with high sensitivity and accuracy. Medication use, and in particular opioid use, is less reliably reported. Vaccination self-report is likely more accurate than EHR data as many vaccinations are not accurately registered. Lay Summary: Inflammatory bowel disease patients' survey responses about recent emergency department (ED) visits, hospitalizations, computerized tomography (CT) scans, corticosteroids, opioids, and vaccinations were compared to medical records. ED visits, hospitalizations, and CT scans were reported accurately, whereas medication use was less reliable. Vaccinations were often unavailable from medical records.